Trastuzumab Potentiates Antitumor Activity of Thiopyrano[2,3-d]Thiazole Derivative in AGS Gastric Cancer Cells - Piotr Roszczenko; Olga Klaudia Szewczyk-Roszczenko; Agnieszka Gornowicz; Robert Czarnomysy; Andrii Lozynskyi; Krzysztof Bielawski; Roman Lesyk; Anna Bielawska (Molecules)
Gastric cancer remains a significant therapeutic challenge, highlighting the need for new strategies to improve treatment efficacy. This study investigates the potential of combined therapy with the novel Thiopyrano[2,3-d]Thiazole derivative LES-6400 and the anti-HER2 antibody trastuzumab in AGS gastric cancer cells. The antitumor effects of the combined therapy were evaluated using various techniques, including the MTT assay for cell viability, [3H]-thymidine incorporation for DNA synthesis, and flow cytometry to assess apoptosis (Annexin V-FITC/PI staining), mitochondrial membrane potential (MMP), and inflammatory cytokine levels. ELISA was employed to measure the levels of IL-6, p53, and cytochrome C. The combination of LES-6400 (1 µM) and trastuzumab (10 µg/mL) demonstrated superior antitumor activity compared to monotherapy with either agent in AGS gastric cancer cells. The combination therapy enhanced apoptosis, presumably by inducing oxidative stress in the cells and disrupting mitochondrial membrane potential. Additionally, a significant increase in p53 protein levels and modulation of interleukin levels, including a marked reduction in IL-6 levels, were observed, suggesting an impact on apoptotic and inflammatory responses. These findings indicate that the combined use of LES-6400 and trastuzumab is a promising therapeutic strategy for gastric cancer, warranting further investigation into the mechanisms of action and potential clinical applications of this combined approach.